Genomic regions of current low hybridisation mark long-term barriers to gene flow in scarce swallowtail butterflies. - Sam Ebdon; Dominik R Laetsch; Roger Vila; Stuart J E Baird; Konrad Lohse (PLoS Genetics)
Many closely related species continue to hybridise after millions of generations of divergence. However, the extent to which current patterning in hybrid zones connects back to the speciation process remains unclear: does evidence for current multilocus barriers support the hypothesis of speciation due to multilocus divergence? We analyse whole-genome sequencing data to investigate the speciation history of the scarce swallowtails Iphiclidespodalirius and I . feisthamelii, which abut at a narrow ( ∼ 25 km) contact zone north of the Pyrenees. We first quantify the heterogeneity of effective migration rate under a model of isolation with migration, using genomes sampled across the range to identify long-term barriers to gene flow. Secondly, we investigate the recent ancestry of individuals from the hybrid zone using genome polarisation and estimate the coupling coefficient under a model of a multilocus barrier. We infer a low rate of long-term gene flow from I . feisthamelii into I . podalirius - the direction of which matches the admixture across the hybrid zone - and complete reproductive isolation across  ≈  33% of the genome. Our contrast of recent and long-term gene flow shows that regions of low recent hybridisation are indeed enriched for long-term barriers which maintain divergence between these hybridising sister species. This finding paves the way for future analysis of the evolution of reproductive isolation along the speciation continuum.